2000
DOI: 10.1007/bf02479650
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation de l'absorption d'eau des bétons comme critères de leur durabilité—Application aux bétons de granulats recyclés

Abstract: RI~SUMI~ A 13 S T R A C TLes granulats issus du recyclage des produits de d4molition s'inscrivent dans le cadre des mat~riaux locaux de substitution, mais leur valorisation dans les b&ons hydrauliques est actuellement frein& par le fait qu'ils sont consid&& comme (~ granulats hors normes >>. On les suspecte ainsi d'avoir des cons4quences ndfastes sur la durabilit~ des b&ons.Les ph~nom~nes de transport, dont l'absorption d'eau par capillarit& s'avhrent &re primordiaux vis ~ vis de la durabilit8 des b&ons ~ base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 4 publications
0
15
0
3
Order By: Relevance
“…In some investigations [10,24], similar values and trends of porosity were found as a function of RCA amount in concrete. In other works [27,31,32], it was found that in concrete with RFA, the amount of water absorbed (implicit porosity) increases.…”
Section: Total Porositymentioning
confidence: 84%
“…In some investigations [10,24], similar values and trends of porosity were found as a function of RCA amount in concrete. In other works [27,31,32], it was found that in concrete with RFA, the amount of water absorbed (implicit porosity) increases.…”
Section: Total Porositymentioning
confidence: 84%
“…Several authors have tested the transport properties of concrete to indirectly characterize its durability [35][36][37][38][39][40][41][42]. Air permeability, electrical resistivity [43] and capillary absorption tests [38,44] are usually regarded as the most appropriate for evaluating concrete durability.…”
Section: Introductionmentioning
confidence: 99%
“…Na Espanha, um estudo analisou os agregados graúdos obtidos a partir de 15 A porosidade, que é uma propriedade que está intimamente relacionada com as propriedades físicas dos agregados, pode ser um critério mais interessante, por influenciar a resistência mecânica e durabilidade dos concretos (CALLISTER, 2000;MEHTA;MONTEIRO, 1994;LIMBACHIA et al, 2000;WIRQUIN et al, 2000).…”
Section: Dificuldades Na Aplicação Das Normas Técnicas Em Usinas De Runclassified